2017
DOI: 10.1039/c7re00039a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of 5-(chloromethyl)furfural (CMF) from high fructose corn syrup (HFCS) using continuous flow processing

Abstract: Demonstrated synthesis of 5-(chloromethyl)furfural (CMF) from both solid sugars and high fructose corn syrup (HFCS) using continuous flow processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Due to the strong shear force generated by centrifugal forces in the CCCS, liquid-liquid mixing is enhanced considerably, accelerating reactions with fast kinetics that are limited by mass transfer. [134] Typically, microreactors have been used for single liquid phase and biphasic (gas-liquid or liquid-liquid) catalytic transformation of biomass derivatives to valuable products using homogeneous or heterogeneous catalysts (e. g., the (biphasic) synthesis of furans from sugars, [135][136][137][138][139][140][141][142][143][144] (aerobic) oxidation, [144][145][146][147][148][149] and hydrogenation of biomass derivatives [144,[150][151][152][153] ). [126] Another intensified reactor configuration for multiphase (gasliquid or liquid-liquid) catalytic biomass transformation is the spinning disc reactor, consisting of a rotating disc around which fluids are fed.…”
Section: Process Intensification For Biomass Conversionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the strong shear force generated by centrifugal forces in the CCCS, liquid-liquid mixing is enhanced considerably, accelerating reactions with fast kinetics that are limited by mass transfer. [134] Typically, microreactors have been used for single liquid phase and biphasic (gas-liquid or liquid-liquid) catalytic transformation of biomass derivatives to valuable products using homogeneous or heterogeneous catalysts (e. g., the (biphasic) synthesis of furans from sugars, [135][136][137][138][139][140][141][142][143][144] (aerobic) oxidation, [144][145][146][147][148][149] and hydrogenation of biomass derivatives [144,[150][151][152][153] ). [126] Another intensified reactor configuration for multiphase (gasliquid or liquid-liquid) catalytic biomass transformation is the spinning disc reactor, consisting of a rotating disc around which fluids are fed.…”
Section: Process Intensification For Biomass Conversionmentioning
confidence: 99%
“…With this, 60 % HMF yield at 91 % fructose conversion could be obtained from the homogeneous acid (0.25 M HCl) catalyzed dehydration of 30 wt% fructose after 2.5-3 min at 180°C in a biphasic aqueous-organic (2 : 3 volume ratio) batch system. [135][136][137][138][139][140][141][142]216] A glass chip-based microreactor was used for the biphasic synthesis of HMF by dehydration of fructose using a mixture of MIBK and 2-butanol as the organic solvent (70/30 wt%) and HCl as the catalyst in the aqueous phase (Table 4, entry 2). [215] By operating such a biphasic system in a microreactor under slug flow operation (Figures 2D, 3B and 5), the superior mixing for an efficient reaction in the aqueous phase is ensured and the extraction rate of HMF towards the non-reactive organic phase is accelerated by the enhanced mass transfer inside droplets/slugs and across the interface (due to internal circulation and high interfacial area available), thus reducing the occurrence of side reactions and increasing the yield and selectivity towards HMF.…”
Section: Homogeneously Catalyzed Furan Synthesis In a Biphasic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of biphasic reaction condition with the addition of an in situ extracting immiscible organic solvent during the reaction exhibited superior results in terms of decreased amounts of humins. Recent discoveries 6,7 showed that using a chlorine source (HCl) favored the formation of 5-chloromethylfurfural (CMF) as opposed to HMF. Let alone leaving a very reactive methyl chlorine moiety in place of the hydroxyl group, this Ox.…”
Section: Figure 3 Possible Derivatives From the Furfural Platformmentioning
confidence: 99%